PEMANFAATAN MEDIA PEMBELAJARAN BERBASIS ELEARNING UNTUK MENINGKATKAN PERKULIAHAN DASAR INSTALASI LISTRIK - Isdiyarto, -; Purwanto, Agus (Jurnal Penelitian Pendidikan, 2010)
Abstract. Education quality can be improved through many ways such as improving lecturer competence, improving curriculum content, improving the quality of learning and evaluation, adequate provision of teaching materials, and adequate provision of facilities and infrastructure. Among those ways, improving the quality of learning occupies a very strategic position. A qualified learning process is expected to improve studentsÃ¢â¬Å¸ learning outcomes. This research is aimed to enhance students understanding of the subject matter of the Basic Electrical Installation subject especially in Domestic Electrical Installations Planning section. This is a classroom action research that comprises two cycle. Keywords: improved understanding